THE INFLUENCE OF PRODUCT INNOVATION AND SERVICE QUALITY ON PURCHASE DECISION ON JAMBI BATIK ASIAH IN DANAU TELUK DISTRICT - Tegar Zaki Hanafi; Ratih Kusumastuti; Derist Touriano (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The aim of this research is to determine the influence of Product Innovation and Service Quality partially influences Purchasing Decisions and the influence of Product Innovation and Service Quality simultaneously on Decisions Purchase. This type of research is quantitative-descriptive. This research was conducted at Batik Jambi Asiah, Danau Teluk Jambi District. The population in this research is all Jambi Asiah Batik consumers in August - October 2023, totaling 105 people. Meanwhile, the research sample consisted of 51 consumers using a purposive sampling technique.